A-star (A*) algorithm implementation for robotics path planning navigation - Emirul Ridzwan, Nor Azmi (2018)
This thesis is about the implementation of Astar (A*) algorithm as path planning algorithm used in robotics navigation. This Astar (A*) algorithm is a smart algorithm which can produce a pathway with a minimum path score avoiding the obstacles within its way. This algorithm also known as the most famous used algorithm in path planning because of its ability to provide a collision-free pathway with a minimum path score. For this project, the main objective is to design and implement an Astar (A*) algorithm. With the used of MATLAB software, the algorithm should be able to provide an optimized pathway and the pathway generated in this software should be a collision-free pathway. In order to provide a real-time map, this project is equipped with a single camera to the prototype of the functional area. This single camera will capture an image of the environment and convert to a black and white map for the algorithm to work on. Other than that, the project used random objects as to provide obstacles in the environment (functional area). At the end of this project, the algorithm functions which to provide a shortest pathway and also a collision-free pathway is verified. The factors (light intensity, colors, position) that may affect the behavior of the Astar (A*) algorithm were identified in the result section in this paper.